Down-Regulation of miRNA-708 Promotes Aberrant Calcium Signaling by Targeting Neuronatin in a Mouse Model of Angelman Syndrome - Vatsa, Naman; Kumar, Vipendra; Singh, Brijesh Kumar; Kumar, Shashi Shekhar; Sharma, Ankit; Jana, Nihar Ranjan (Frontiers in Molecular Neuroscience, 2019)
The expression of ubiquitin ligase UBE3A is paternally imprinted in neurons and loss of function of maternally inherited UBE3A causes Angelman syndrome (AS), a neurodevelopmental disorder characterized by severe intellectual disability and motor disturbances. Over activation of UBE3A is also linked with autism. Mice deficient for maternal Ube3a (AS mice) exhibit various behavioural features of AS including cognitive and motor deficits although the underlying molecular mechanism is poorly understood. Here, we investigated possible involvement of miRNA in AS pathogenesis and identified miR-708 as one of the down-regulated miRNA in the brain of AS mice. This miR-708 targets endoplasmic reticulum resident protein neuronatin (a developmentally regulated protein in the brain) leading to decrease in intracellular Ca2+. Suppression of miR-708 or ectopic expression of neuronatin increased the level of intracellular Ca2+ and phosphorylation of CaMKIIα at Thr286. Neuronatin level was significantly increased in various brain regions of AS mice during embryonic and early postnatal days as well as in parvalbumin-positive GABAergic neurons during adulthood with respect to age-matched wild type controls. Differentiated cultured primary cortical neurons obtained from AS mice brain also exhibited higher expression of neuronatin, increased intracellular basal Ca2+ along with augmented phosphorylation of CaMKIIα at Thr286. These results indicate that miR-708/neuronatin mediated aberrant calcium signalling might be implicated in AS pathogenesis.